Bridging the island : Brazilians' views of Spanish America and themselves, 1865-1912 - Preuss, Ori (Tiempo emulado ;, 2011)
Explores the interplay between Brazilian interpretations of the national Self and the Spanish-American Other during the critical years spanning the demise of slavery and monarchy.